Hypertonic Saline Versus Isotonic Saline in Septic Shock (Effects on Morbidity, Mortality, and Clinical Outcome) - Hassan S. Effat; Sayed S. Ramadan; Mohamed S. Mokhtar; Moataz M. Ibrahim (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Septic shock remains an impatient cause of morbidity and mortality. A cascade of inflammatory mediators released cause misdistribution of blood flow and organ perfusion. Early restitution of the circulation by fluid administration either crystalloid or colloid solution improve tissue oxygen delivery and increase survival. Aim of work This study is a prospective randomized single center study its main objective is to investigate the therapeutic value of hypertonic saline in patients with septic shock. Patients and methods Forty critically ill patients admitted with septic shock divided into two groups, the first group received isotonic saline and hydroxylthyl (control group) starch, while the second received hypertonic saline 3% in addition to isotonicsaline and hydroyethyl starch. Results Our study results showed that hypertonic saline administration in septic shock patients is safe and can be used as an adjuvant resuscitation fluid therapy as it has a rapid and prolonged effect on those patients hemodynamics or plus it showed significant anti-inflammatory action and also it improve all cardiac functions although this improvement was transient as was the improvement in mortality, intensive care unit stay, need for mechanical ventilator use of inotropes and vasopressors and the scoring system evaluation. Discussion Hypertonic saline 3% is safe and can be used in resuscitation of septic shock patients.